Stem cell-like circulating tumor cells indicate poor prognosis in gastric cancer - Wang Yi-Wen; Li Long-Long; Lu Ming; Li Hao; Hu Kong-Wang (Archives of Medical Science, 2020)
Introduction Circulating tumor cells (CTCs) have the characteristics of cancer stem cells and play an important role in the recurrence and metastasis of tumors. CD44 is a surface marker molecule for gastric cancer stem cells (GCSCs) and can be used to identify and isolate GCSCs. Here, we investigated the effect of CD44 protein expression, circulating tumor cells, and CD44-positive CTCs on the prognosis of gastric cancer (GC).